Tradicija (kratkega) pripovedništva v slovenščini pred 1820 - Perenič, Urška (Jezik in slovstvo, 2020)
In this article, we first define the concept of short story telling before 1820. Short story telling is understood as written texts that include religious and secular narrative verse and narrative prose. We do not draw a sharp distinction between translated and original writing, as Slovenian literary culture of this period (and later periods) is characterised by intensive intercultural contacts with other languages (Latin, German, Italian). We propose the notion of "exemplary storytelling" (Schwarzbach-Dobson), which, on the basis of the predominantly educational function of texts, combines various short forms of narration, from Biblical stories to parables, anecdotes to fictional stories. We consider both religious texts (e.g., sermons) and secular texts (e.g., almanacs), and demonstrate the continuity of exemplary storytelling in Slovenian from Protestantism onwards. The findings are summarised in an original typology that contains the main manifestations of exemplary storytelling.
Keywords: anekdota; balada; basen; eksempelsko pripovedovanje; katoliška doba; kratkočasna zgodba; krištofšmidovska pripoved; legendarna pesnitev; poučno-vzgojna funkcija književnosti; pridiga; prilika; prispodoba; protestantizem; razsvetljenstvo; Schmid, Christoph; slovenska književnost; starejša slovenska književnost; svetopisemske pripovedi